Inclusive recreation programs and services for diverse populations (Human Kinetics, 2010)
Everyone should have the opportunity to enjoy the benefits of recreation. As the demographics of our communities continue to change and expand, it will be more important than ever for recreation professionals to be prepared to provide access to anyone and everyone who wants to participate. In Inclusive Recreation: Programs and Services for Diverse Populations, students will learn to provide programs and services not only to individuals with disabilities but also to people of both sexes and all ages, cultures, ethnicities, races, and religions. Written by 26 leading professors and professionals in the field, Inclusive Recreation provides the knowledge and skills that students will need in their careers to ensure that all people will be able to participate in the recreation programs they provide. The book features the following: The latest acknowledged theories in inclusion, as well as information on history, legislation, and cultural competence, to serve as the basis for students' understanding of the field Strategies for becoming more conscious of diversity and disability and using appropriate language and communication skills so that students will be better prepared to consider and work with everyone in their community A thorough discussion of universal design in both facilities and services to help students plan inclusive experiences that appeal to the broadest possible audience Chapters on specific service areas, including sports, fitness and wellness, outdoor and adventure, arts and culture, aquatics, and tourism, so students will have a better feel for how inclusion strategies work in various programs; Inclusive Recreation also helps students learn more about the groups they'll likely meet as professionals. They'll look at the socio-demographic characteristics of each group, the factors that affect their recreation participation, and approaches for serving the needs of each population. They'll also be encouraged to examine their own biases and think about how those biases could affect their ability to provide services to their clients. In addition, students will find information on staff training, designing respectful accommodations, and marketing, including pricing, promotion, and evaluation of service quality. Throughout the book are examples of inclusive practices from a variety of sectors to help students understand how inclusion strategies work in real programs. Spotlight on Inclusive Recreation Programs sidebars highlight best practices from various countries, including Australia, Brazil, Canada, Japan, and the United Kingdom. Each spotlight includes a description of the program, a short history, and information on who is served by the program. Professionals in Action sidebars introduce professionals who have contributed to inclusive practices and help students explore their career options. Inclusive Recreation offers theory and practical applications to prepare students to implement inclusive facility access, training, programming, and services for a variety of recreation activities. Readers will consider how recreation, leisure, and tourism activities can become accessible to all the community members they serve.